Determination of the Endocannabinoids Anandamide and 2-Arachidonoyl Glycerol with Gas Chromatography-Mass Spectrometry: Analytical and Preanalytical Challenges and Pitfalls - Christian Lanz; Johan Mattsson; Felix Stickel; Jean-Francois Dufour; Rudolf Brenneisen (Medical Cannabis and Cannabinoids)
Background: The endocannabinoids anandamide (N-arachidonoyl ethanolamide [AEA]) and 2-arachidonoyl glycerol (2-AG) are involved in the regulation of neuronal, immune, metabolic, vascular, and reproductory functions. Methods: The development and validation of an analytical method for the determination of AEA and 2-AG in human plasma based on liquid-liquid extraction and gas chromatography-mass spectrometry after silylation is described and (pre)-analytical pitfalls are identified. Results: In contrast to 2-AG, AEA was unstable in whole blood and increased by a factor of 2.3 within 3 h on ice. AEA was stable in plasma on ice for 4 h while 2-AG tended to decrease. Excellent stability at room/ambient temperature was found for both derivatized compounds over 45 h. Furthermore, 3 freeze-thaw cycles revealed a complex pattern: endogenous AEA was stable in plasma but slightly increased in spiked samples (+12.8%), while endogenous 2-AG concentrations increased by 51% and declined by 24% in spiked samples. A long-term study over 4 weeks at –80°C showed that low endogenous AEA and spiked 2-AG concentrations were stable. However, spiked AEA tended to increase (+19%) and endogenous 2-AG significantly increased by 50% after 2 weeks. Food intake 2 h before blood collection showed no effect on AEA concentrations, whereas 2-AG increased significantly by a factor of 3. Conclusions: Overall, limited in vitro and/or in vivo/ex vivo chemical stability of endocannabinoids has to be taken into account.